Estudo da interação do 17β-estradiol com óxido de grafeno via simulação ab initio e avaliação experimental - Oliveira, Patricia Viera de (2019)
Currently, the detection of substances called endocrine disrupters in sewage treatment plants, rivers and in drinking water itself is a matter of global concern. To alleviate this problem, it is necessary to apply additional treatments in the water; one of them is the adsorption, which has been proving to be a promising method with high efficiency. One of the nanoadsorbents that has stood out is graphene oxide, its great ability to adsorb pollutants and its exceptional structural and electronic properties. Thus, the objective of this work is to evaluate, through computational and experimental simulation, the use of graphene oxide for the adsorption of 17β-estradiol and 17α-ethynylestradiol endocrine disrupters, both of natural and synthetic origin, respectively. We performed ab initio calculations by means of computational simulations in order to improve the understanding of the structural, electronic and magnetic characteristics. In parallel, the experiments evaluated the adsorption efficiency by analyzing adsorption kinetics, adsorption isotherms varying the proportion of co solvent (methanol) present in solution. The theoretical results showed that the interaction between graphene oxide and endocrine disrupters, and graphene oxide and methanol, occurred through physical adsorption, mainly due to the π-π type interactions and hydrogen bonds between the systems. This is confirmed by the experimental data, in which the highest absorption rate was 98:2% (m/m) of water and methanol, the temperature of 288K and qmax=169.49 mg/g, and the adsorption isotherm model that most adapted to the model was Langmuir, and when analyzing the kinetics of adsorption, the kinetics of pseudo second order is the one that best suits the systems studied. It was observed that the increase in the adsorption capacity of 17β-estradiol in the nanomaterial, since the methanol occupies active sites of the graphene oxide reducing the specific area for the adsorption of the endocrine disrupters. The results obtained in this study provide subsidies for a better understanding of the physicochemical properties of the interactions evaluated. Based on the results obtained experimentally and by means of ab initio calculations, it is observed that graphene oxide is a promising material for the removal of 17β- estradiol in aqueous solution and the effect of the co-solvent methanol must be taken into account when performing adsorption experiments.